Primary Malignant Melanoma of the Rectum: Report of Two Cases. (18th December 2012) - Tomioka, Kodai; Ojima, Hitoshi; Sohda, Makoto; Tanabe, Akiko; Fukai, Yasuyuki; Sano, Akihiko; Fukuda, Takahiro; Murakami, Masahiko
Abstract : We report two cases of rectal malignant melanomas. The patients were an 84-year-old male and a 66-year-old female who had blood in their stools. They were preoperatively diagnosed with poorly differentiated adenocarcinoma of the rectum. The clinical diagnosis for each was rectal carcinoma at stage IIIc according to the tumor-node-metastasis classification (6th edition), and the patients underwent abdominoperineal resection with dissection of lymph nodes. Pathological examination of the resected specimens revealed a malignant melanoma. Immunohistochemical analysis results were positive for HMB-45 and negative for cytokeratin AE1/AE3, CD45, and synaptophysin. Primary anorectal melanoma is an uncommon and aggressive disease that carries a poor prognosis. Therefore, it is necessary to provide systemic treatment. To improve prognosis, it is important to detect anorectal melanoma at an early stage.